Penerapan Asesmen Kinerja untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Kognitif Siswa - Ambarwati, Lilies (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The purpose of this study was to find out that the application of performance assessments can improve science process skills and cognitive learning outcomes for grade VII students of SMP Negeri 5 Demak in the 2017/2018 academic year. The subjects of this study were seventh grade students of SMP Negeri 5 Demak. The type of research used is Classroom Action Research (CAR), using two cycles. The technique of collecting data was by observing the implementation of the scientific process and testing cognitive learning outcomes as many as 20 questions. The instruments used in this study were implementation test sheets (RPP), science process skills observation sheets, and student cognitive learning outcomes test sheets. The data on the results of the RPP implementation test in the first cycle was 68% at the first and second meetings in the good category, and in the second cycle it was 100% at the first and second meetings in the very good category. The data on the results of science process skills in the first cycle was 55% with a fairly high category, and 75% in the second cycle was included in the high category. Meanwhile, in the cognitive learning outcomes of students, the average value of the first cycle was 66 with classical completeness achieved by students of 40%, and in the second cycle of 77 with classical completeness achieved by students of 90%. Thus, it can be concluded that the application of performance assessments can improve science process skills and cognitive learning outcomes for grade VII students of SMP Negeri 5 Demak in the 2017/2018 academic year.